SCENARIOS OF TRANSFORMATION OF THE BANKING SYSTEM UNDER THE INFLUENCE OF INNOVATIONS: UKRAINIAN SPECIFICITY - Anatolii O. Zadoia; Alisa S. Mahdich; Oleksandr A. Zadoia; Yurii A. Zadoia (Academy Review)
Innovativeness is an integral feature of the modern economy, particularly in the banking sector. The authors of this article aimed to identify potential scenarios for the transformation of the banking system under the influence of innovations and increased competition from fintech organizations. They sought to explore the components of the market mechanism for the self- regulation of innovative activities in commercial banks, the tools and methods of state influence on these processes, and, based on a study of global experience, to justify proposals for intensifying the introduction of innovations by commercial banks in Ukraine. The study examined five possible scenarios for the transformation of Ukraine’s banking system: (1) modernization of existing banks using the latest technologies, allowing them to maintain relationships with clients; (2) replacement of traditional banks with new (neo-banks) that operate under a different business model; (3) fragmentation of financial services between specialized fintech companies and traditional banks; (4) banks being pushed out of direct client relationships and becoming service providers; and (5) the complete displacement of traditional banks, replaced by other structures. The analysis of transformations in Ukraine’s banking system revealed elements of each of these scenarios without the dominance of any single one. Fintech companies operate according to the “niche” principle, targeting untapped market segments, services, or technologies in an effort to succeed. Banks, in contrast, tend to be more conservative, a result of the greater regulation governing their activities. However, the development of payment systems in Ukraine demonstrated that fintech companies initially dominated this sector until large banks entered the market and displaced other players. In reality, banks have more resources (both financial and organizational) to introduce certain innovative products or technologies. The successful implementation of these innovations will depend largely on the interplay between the market mechanism of self-regulation and state regulation. Following the principles outlined in the research for state innovation policy will enhance its effectiveness and facilitate the integration of Ukraine’s banking system into European and global financial markets.